1997
DOI: 10.1002/marc.1997.030181215
|View full text |Cite
|
Sign up to set email alerts
|

Threading of cyclodextrins onto a polyester of octanedicarboxylic acid and polyethylene glycol

Abstract: A water-soluble polyester was synthesized from dimethyl octane-1,8-dicarboxylate and polyethylene glycol (a,, = 900). This polymer forms water-soluble inclusion compounds with a-, p-and hydroxypropyl-a-cyclodextrin as proven by surface tension measurements, 'H NMR spectroscopy and titration microcalorimetry. Mainly the octamethylene segments were covered by the cyclodextrins. This inclusion can be used to increase the solubility and the critical micelle concentration of the polyester in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 13 publications
4
41
0
Order By: Relevance
“…Temperature-dependent complexations with CDs have been extensively studied 101,[165][166][167] due to their ability to produce supramolecular structures of desired architectures. [58][59][60][61][168][169][170][171] In general, the rate of complexation of polymer with CD increased significantly with increasing temperatures.…”
Section: Temperature-responsive Inclusion Complexesmentioning
confidence: 99%
“…Temperature-dependent complexations with CDs have been extensively studied 101,[165][166][167] due to their ability to produce supramolecular structures of desired architectures. [58][59][60][61][168][169][170][171] In general, the rate of complexation of polymer with CD increased significantly with increasing temperatures.…”
Section: Temperature-responsive Inclusion Complexesmentioning
confidence: 99%
“…Wenz et al [27] studied the complexation of a water-soluble polyester of octanedicarboxylic acid and poly(ethylene glycol) with a-, b-and hydroxypropyl-a-CD in aqueous solutions and reported the solubility change of this polymer which they attributed to the partial coverage of the polymeric guest with CD rings. So far, there are no reports on the inclusion complex formation of methylated-b-CDs with unsaturated polyesters.…”
Section: Resultsmentioning
confidence: 99%
“…Wenz et al reported inclusion complexation behavior between cyclodextrins and some organic polymers [108][109][110].…”
Section: Complexation With Polymermentioning
confidence: 98%